Reanimating feminist archives: ethics and praxis - Webb, Sharon; Thomson, Rachel; Moore, Niamh (Frontiers in Communication, 2024)
This paper explores the complexities of developing feminist archives. It focuses on the 'Feminist Approaches to Youth Sexuality (FAYS)' archive, developed as part of the Reanimating Data project (RAD, 2018-21). Through this case study, we explore the ethical considerations and practices involved in reanimating a landmark feminist study, the Women, Risk, and AIDS Project (WRAP), and emphasise the ethical dimensions of reanimation processes, considering feminist ethics of care and risk. We also explore the concept of rematriation, which is rooted in indigenous feminist scholarship, and which has become a guiding principle in our efforts to return WRAP to its geopolitical context. As such, the paper is structured in 3 sections: data in the attic, on recovery and rematriation; feminist ethics, on care and risk; feminist archival praxis, on reanimating and language.